The unconformity caused by the Huaiyuan movement and the deep natural gas exploration field in the Ordos Basin, China - Huaqing Liu; Xiangbo Li; Yuhu Ma; Yunlai Bai; Junping Huang (Natural Gas Industry B, 2021)
In order to clarify the hydrocarbon accumulation significance and exploration prospect of the unconformity caused by the Huaiyuan movement in the Ordos Basin, this paper studies the spatial distribution and structural plane characteristics of this unconformity and its relationships with hydrocarbon accumulation by observing field outcrops and cores and analyzing logging data, based on the previous research results and the interpretation results of 2D and new 3D seismic data. And the following research results are obtained. First, the unconformity was mainly formed in the Floian Age of Early Ordovician and widely occurs at the bottom of the Jiawang Formation and the top of the Sanshanzi Formation and the related tectonism lasts 30 Myr. Second, basal conglomerate and sandstone less than 1 m in thickness are developed above the unconformity at the edge of the basin, while thin mudstone, argillaceous dolomite (limestone) and marl are developed above the unconformity in the central part of the basin. Third, the unconformity structurally consists of three layers, including a basal conglomerate layer, a paleosoil layer and a fully–semi weathered carbonate layer from top to bottom, among which, the last one is 20–90 m in thickness with developed dissolution fractures and pores to form a quality reservoir. Fourth, the unconformity results in the development of a series of large valleys landforms, which incise the Lower Ordovician–Upper Cambrian. Fifth, the unconformity can act as a good channel for hydrocarbon migration, and it connects with the unconformity caused by the Caledonian movement within the paleo-uplift of the Ordos Basin, which is favorable for the the hydrocarbon of different sources in the west side of the basin eastwards to migrate, accumulate and form a gas reservoir. In conclusion, the deep Lower Paleozoic related to the Huaiyuan unconformity is expected to be an important natural gas exploration field in the Ordos Basin.